Perjalanan Emosional Remaja di Salah Satu Panti Asuhan Medan - Putri, Neysa Aulia; Lubis, Mia Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Orphanages in Indonesia play an important role in supporting children who do not have families, helping them develop well. These children are cared for by caregivers who act as substitute parents, with the hope that they can blend in and socialize in a diverse environment. However, adolescents in orphanages often face emotional problems, such as difficulties in expressing feelings and seeking social support, which can affect their mental health. This study uses qualitative methods to understand the emotional journey of a 17-year-old adolescent in an orphanage in Medan, with a focus on micro-interventions to help manage her emotions.